Hubungan Hukum Pekerja dan Keberlakuan Peraturan Perusahaan dalam Perusahaan Konglomerasi - Windi Afdal; Carina Tan (Fakultas Hukum, Universitas Internasional Batam, 2019)
This thesis reviewed about the legal relations of workers and the enactment of company regulations in conglomeration companies if contract of the workers in the parent company are transferred to other subsidiaries which are conglomeration companies with equal ownership or the existence of a very special relationship. The role of company regulations is very important in resolving industrial disputes where the existence of company regulations in every company in a conglomeration company will guarantee the rights between workers and the company in writing. In this thesis, Researcher finds that conglomeration companies include PT. AG, PT. TMI, PT. GCS and PT. KTI, that the Company Regulations are only owned by the First Company, which is PT. AG, but not owned by others. Then Researcher found out that the employees which status is PWKTT who had worked 3 years in the First Company were transferred by the management of the conglomeration company to the Next Company to avoid the status of PKWT.